Overexpression of PCNA Attenuates Oxidative Stress-Caused Delay of Gap-Filling during Repair of UV-Induced DNA Damage - Yi-Chih Tsai; Yi-Hsiang Wang; Yin-Chang Liu (Journal of Nucleic Acids)
UVC irradiation-caused DNA lesions are repaired in mammalian cells solely by nucleotide excision repair (NER), which consists of sequential events including initial damage recognition, dual incision of damage site, gap-filling, and ligation. We have previously shown that gap-filling during the repair of UV-induced DNA lesions may be delayed by a subsequent treatment of oxidants or prooxidants such as hydrogen peroxide, flavonoids, and colcemid. We considered the delay as a result of competition for limiting protein/enzyme factor(s) during repair synthesis between NER and base excision repair (BER) induced by the oxidative chemicals. In this report, using colcemid as oxidative stress inducer, we showed that colcemid-caused delay of gap-filling during the repair of UV-induced DNA lesions was attenuated by overexpression of PCNA but not ligase-I. PCNA knockdown, as expected, delayed the gap-filling of NER but also impaired the repair of oxidative DNA damage. Fen-1 knockdown, however, did not affect the repair of oxidative DNA damage, suggesting repair of oxidative DNA damage is not of long patch BER. Furthermore, overexpression of XRCC1 delayed the gap-filling, and presumably increase of XRCC1 pulls PCNA away from gap-filling of NER for BER, consistent with our hypothesis that delay of gap-filling of NER attributes the competition between NER and BER.